Tonic modulation of GABA release by nicotinic acetylcholine receptors in layer V of the murine prefrontal cortex - Aracri, Patrizia; Consonni, Silvia; Morini, Raffaella; Perrella, Marco; Rodighiero, Simona; Amadeo, Alida; Becchetti, Andrea (Cerebral cortex (New York, N.Y. 1991), 2010)
By regulating the neocortical excitability, nicotinic acetylcholine receptors (nAChRs) control vigilance and cognition and are implicated in epileptogenesis. Modulation of gamma-aminobutyric acid (GABA) release often accompanies these processes. We studied how nAChRs regulate GABAergic transmission in the murine neocortex with immunocytochemical and patch-clamp methods. The cholinergic fibers densely innervated the somatosensory, visual, motor, and prefrontal cortices (PFC). Laminar distribution was broadly homogeneous, especially in the PFC. The cholinergic terminals were often adjacent to the soma and dendrites of GABAergic interneurons, but well-differentiated synapses were rare. Tonically applied nicotine (1-100 microM) increased the frequency of spontaneous GABAergic inhibitory postsynaptic currents (IPSCs) on pyramidal neurons in PFC layer V. The contribution of nAChR types was assessed by using 1 microM dihydro-beta-erythroidine (DHbetaE), to block heteromeric nAChRs, and 10 nM methyllycaconitine (MLA), to block homomeric nAChRs. Both inhibitors antagonized the effect of nicotine on IPSCs, suggesting that mixed nAChR types control pyramidal neuron inhibition in layer V. To determine whether nAChRs are expressed on basket cells' terminals, we studied miniature IPSCs (mIPSCs). These were revealed using 0.5 microM tetrodotoxin and 50 microM Cd(2+) to isolate the GABAergic terminals from the action potential drive. The nicotinic stimulation of mIPSCs was antagonized by DHbetaE, but not MLA, indicating that heteromeric nAChRs prevail in GABAergic terminals. Immunocytochemistry confirmed the expression of nAChRs on basket cells' somata and terminals. Finally, when the ionotropic glutamatergic transmission was blocked, nicotine partially inhibited the IPSCs, an effect counteracted by both DHbetaE and MLA. Therefore, a fraction of nAChRs are capable of activating GABAergic interneurons that in turn inhibit other GABAergic interneurons, thereby reducing the IPSCs. We conclude that heteromeric nAChRs control GABA release presynaptically, whereas mixed nAChRs regulate both excitation and inhibition of interneurons, the balance depending on the overall glutamatergic drive.